The effectiveness of six sigma method in manufacturing company / Rosedhila Ramli and Farrahshaida Mohd Salleh - Ramli, Rosedhila; Mohd Salleh, Farrahshaida (2003)
Final project is part of our course, structure that needs to be taken to complete our diploma, by a student that is in the final years. This project has been required to finish in two semesters, the main propose that all mechanical student have to take this course is to give us opportunity to test our skill and to gather all the knowledge that we have been studying for this few years. From this kind of course, we can figure out the best way to improve our knowledge for the purpose of using in the future. Nowadays, many industries have to use any methods or trends to control their quality of product. The latest trend is six sigma. Six sigma is one of the trends to control and reduce the defect in production of quality. So we choose this project because it is important to exposure to diploma student. Six sigma is capitalizes on employee involvement - reduce eight form of waste. It enables entire company to problem solve. From this, it can help the company to achieve their goals in production system. The important things, six sigma is a waste reduction, customer focused, and business results oriented improvement program.